The Role of Water Resources Management in Reducing the Production Costs of Agricultural Products - Kariznovi, Ali (2021)
In order to achieve the goals of sustainable agricultural and rural development, agricultural education is an issue that should be in base considered and researched according to the importance of the issue and its related challenges must be realistically analyzed, Since water is one of the effective factors in the agricultural sector that plays a vital role in the production of agricultural products. There are several factors for low water productivity in the country, one of which can be considered non-optimal and unplanned use of water. It is clear that by increasing the level of awareness of farmers about the type of management of agricultural water resources it is possible to reduce current expenses and then to achieve high productivity and increasing income from crops and orchards. Therefore, in this study, the optimal management of water and reduction of production costs in the agricultural sector in Zabrkhan county of Neishabour city has been studied. The research method in this article was a descriptive- analytical method and the data was collected by two methods of library and field methods. The results show that the production cost per hectare of all crops in lands under water resources management is less than unmanaged lands. This rate varied between 3.4 to 16.8 percent. If we associate this reduction in production cost with product efficiency and use the cost per kilogram of production as a criterion, the reduction will be 165.2% for irrigated wheat, 150% for irrigated barley, 106.8% fodder corn and 54.4% for garden products. Therefore, according to the research results, the research hypothesis is confirmed.